CONTINENTAL GEOTHERM AND THE EVOLUTION OF RIFTED MARGINS - Reston T.J.; Morgan J.P. (My University, 2004)
Models of melting accompanying mantle upwelling predict far more melt than is observed at nonvolcanic margins. The discrepancy may be explained if the paradigm of a uniform asthenosphere is incorrect. Work on the velocity structure of the continents has shown that the convecting sublithospheric mantle may have a potential temperature as low as 1200 °C, ˜100 °C cooler than that beneath the oceans. The continental geotherm derived from studies on xenoliths brought up by kimberlites is also compatible with a cool sublithospheric mantle except where perturbed by mantle plumes. Upwelling of such cool mantle during rifting leads to little melt production, even for rapid extension rates, explaining the formation of amagmatic margins away from mantle plumes. However, the transition to seafloor spreading and the development of normal-thickness oceanic crust requires the invasion of the amagmatic rift by hotter oceanic asthenosphere and/or plume material. This influx may cause a transient thermal uplift, recorded as a breakup unconformity. Conversely, at volcanic margins, the onset of seafloor spreading is accompanied by the escape of the hot plume puddle along the mid-ocean ridge system away from the volcanic margin, leading to a pulse of rapid subsidence.
Keywords: rifting; breakup; geotherm; melting; mantle; unconformity